Potencial mutagénico y genotóxico de augas residuales de la curtiembre tasajero en la ciudad de Cúcuta, Norte de Santander, Colombia (2015)
Tanning is an industrial process that requires large volumes of water for the transformation of a putrescible material into a non-putrescible one, suitable to be used in manufactured products. The wastewater generated by this industry are generally discharged without previous treatment into water bodies, generating large amounts of biochemical demands of oxygen and chemical oxygen, high pH values, presence of toxic chemical substances that act as mutagens, increasing the risk of developing cancer in the exposed population. In the town of Cúcuta small tannery industries exist, which do not dispose the basic tools or knowledge regarding the proper waste treatment, therefore generating pollution of water, which afterwards can be used by the population. In the chemical process of this industry, chromium, lead, sulfides, zinc chromates and calcium, compounds considered among the most potent human carcinogens are used. The study included the analysis and determination of the mutagenicity and genotoxicity of wastewater from the tannery “Tasajero”. Revista U.D.C.A Actualidad & Divulgación Científica 18 (1): 13 - 20Enero - Junio 201514For genotoxicity determination the comet assay was used; for the mutagenicity analysis, the Ames test with Salmonella typhimurium strains TA98 and TA100 was employed. It was found that the wastewater from the evaluated tannery induces DNA damage in human lymphocytes. Similarly, the results indicate that this water increased the mutagenicity in the TA98 strain.